Performance assessment in strength and conditioning - Comfort, Paul PhD, CSCS*D, ASCC; McMahon, John J. PhD, CSCS, ASCC; Jones, Paul A. PhD, MSc, BSc (Hons), CSCS*D, BASES Accred. CSci (Routledge, Taylor & Francis Group, 2019)
"It is an essential skill for any strength and conditioning coach to be able to reliably assess the physical performance of their athletes and communicate the results and their implications to performers and coaches, alike. Performance Assessment in Strength and Conditioning is the first textbook to clearly and coherently suggest the most appropriate and reliable methods for assessing and monitoring athletes' performance, as well as including detailed sections on testing considerations and the interpretation and application of results"--